2021
DOI: 10.1590/0037-8682-0195-2020
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with social isolation and loneliness in community-dwelling older adults during pandemic times: a cross-sectional study

Abstract: Introduction: Psychosocial aspects need to be discussed in the context of the Covid-19 pandemic. Currently, no studies have investigated the factors associated with social isolation and loneliness among community-dwelling older adults. Therefore, this study analyzed the association of social isolation and loneliness with socioeconomic, clinical, and health characteristics, and Covid-19-related variables, among community-dwelling older adults during the pandemic. Methods: A cross-sectional study was conducted v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
(42 reference statements)
2
12
0
3
Order By: Relevance
“…The literature has shown that older adults living with cognitive deficits enjoy and benefit from interacting in activities such as dancing, storytelling, clowning, and exchanging cooking recipes. 22 , 23 , 24 , 25 , 26 The combination of activities is in line with authors who propose that carrying out community person‐centered holistic interventions demands creativity and innovation from healthcare teams. 33 …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The literature has shown that older adults living with cognitive deficits enjoy and benefit from interacting in activities such as dancing, storytelling, clowning, and exchanging cooking recipes. 22 , 23 , 24 , 25 , 26 The combination of activities is in line with authors who propose that carrying out community person‐centered holistic interventions demands creativity and innovation from healthcare teams. 33 …”
Section: Discussionsupporting
confidence: 67%
“…Additionally, loneliness is also associated with declines in motor function and systemic arterial hypertension in the Brazilian older adult population. 22 According to a study conducted with Brazilian older adults during the pandemic, individuals who reported interacting frequently outside home and individuals who felt that their virtual interactions were disconnected presented increased loneliness. Lonely Brazilian older adults could be at greater risk for COVID‐19 because they would be less prone to comply with physical isolation recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Otras investigaciones ven a las personas adultas mayores y a los cuidadores como una preocupación social, ya que demandan servicios de salud y ayuda de cualquier índole (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Algunas ven la necesidad de investigar más esta etapa de la vida, donde pueden aportar elementos más certeros para el cuidado en la familia y en los ámbitos de servicios de salud, política, sociales y educación (52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Publicaciones Según Objeto De Estudio Bases De Datos Y País ...unclassified
“…Complicaciones más frecuentes en las personas adultas mayores y cuidado-res: se resaltan aspectos como que el distanciamiento físico y el aislamiento social no solo tienen un gran impacto en la salud mental, sino también en la salud física y su funcionamiento (14). Otro aspecto importante es la incidencia de la soledad en las personas adultas mayores que, a su vez, está relacionada directamente con diversos factores como la ansiedad, la preocupación por ser infectados y la tensión financiera debido a la pandemia (17,(51)(52)(53)59). Además, hay una gran necesidad de implementar una legislación adicional para reforzar la protección de las personas adultas mayores trabajadoras y de los cuidadores (44).…”
Section: Tipo De Publicaciones Científicas Y Temas Relacionados Con L...unclassified
See 1 more Smart Citation